2013
DOI: 10.1021/am401210w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu2ZnSnS4 Thin Films by a Precursor Solution Paste for Thin Film Solar Cell Applications

Abstract: Cu2ZnSnS4 (CZTS) is a very promising semiconductor material when used for the absorber layer of thin film solar cells because it consists of only abundant and inexpensive elements. In addition, a low-cost solution process is applicable to the preparation of CZTS absorber films, which reduces the cost when this film is used for the production of thin film solar cells. To fabricate solution-processed CZTS thin film using an easily scalable and relatively safe method, we suggest a precursor solution paste coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 16 publications
4
67
0
Order By: Relevance
“…Sudip K. Saha et al prepared CZTS-fullerene hybrid p-n junction solar cells by hot injection method and have reported 0.9% PCE [5]. Jin Woo Cho et al reported the PCE of 3.02% for spin coated CZTS thin films [6]. Subramaniam et al have reported 1.34% PCE for CZTS film deposited by chemical bath deposition method [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sudip K. Saha et al prepared CZTS-fullerene hybrid p-n junction solar cells by hot injection method and have reported 0.9% PCE [5]. Jin Woo Cho et al reported the PCE of 3.02% for spin coated CZTS thin films [6]. Subramaniam et al have reported 1.34% PCE for CZTS film deposited by chemical bath deposition method [2].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fast depletion of indium reservoir is another concern for the sustainable growth [4][5][6]. Due to these reasons more attention has been paid in recent years to the semiconductors, based on less toxic, earth abundant elements such as copper zinc tin sulphide (CZTS) and (CZTSe) [7][8][9][10][11][12][13][14][15][16]. This films of CZTS and CZTSe are deposited readily by radio frequency (RF) and diode (DC) magnetron sputtering technology and the corresponding solar cells deliver efficiency better than 10% with a good stability [13,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…28 More interestingly, Agrawal and co-workers indicated that the use of wurtzite-derived CZTS nanoparticles has the potential to remove the unsintered layer in kesterite CZTSSe solar cells. 29 For the CZTSSe solar cells fabricated by the nanocrystal-based ink method and the non-hydrazine molecular precursor solution approach, there is always a largegrain self-termination problem during the selenization processes, [15][16][17][18]22,23 which will lead to an undesirable smallgrained bottom layer; therefore, it is highly urgent to develop a low-cost and facile approach to overcome the fine-grained layers in selenized CZTSSe films. In this paper, we present a simple and powerful strategy to significantly enhance grain growth in CZTSSe absorber layers by insetting Sb 2 S 3 , CuSbS 2 , and NaSb 5 S 8 thin films.…”
Section: ■ Introductionmentioning
confidence: 99%